Penser l’informel à l’aune de contextes d’enseignement-apprentissage dits formels - Éric Navé (Recherches en didactique des langues et des cultures)
The objective of this contribution is to reflect on the informal nature of several fields of language and culture teaching (DLC in French), or rather of certain informal aspects of those fields. However, the field of « didactics » is considered formal by theorists of the informal and theorists of « didactique des langues » consider non-institutional situations as excluded from their field of research. This said, we aim in this paper for a more refined understanding of the informal sector and propose a typology in the light of the DLC. For this purpose, we rely on two asynchronous online forums that we set up as a teacher between the end of 2019 and half of the year 2020 for the benefit of FFL adult false-beginners from the Arab Open University and the Alliance Française in Jeddah, KSA. We rethink and redefine the field of the informal with regard to the notion of power in particular.